Case report: Radiologic findings of retroperitoneal malignant mesenchymoma - Ozdemir, Hüseyin; Kiriş, Adem; Kocakoç, Ercan; Boztosun, Yasemin (My University, 2003)
Malignant mesenchymomas are rare soft tissue tumors that contain two or more distinct histologic subtypes of sarcoma within the same tumor. Although experience with these tumors is limited, they are generally considered high grade neoplasms and are associated with a poor prognosis. Here we present radiologic findings of a case with malignant mesenchymoma in the retroperitoneum.
Retroperitoneal malign mezankimomanin radyolojik bulgulari.
Keywords: Aged; Diagnosis, Differential; Female; Humans; Magnetic Resonance Imaging; Mesenchymoma; Retroperitoneal Neoplasms; Tomography, X-Ray Computed; aged; article; case report; computer assisted tomography; differential diagnosis; echography; female; human; mesenchymoma; nuclear magnetic resonance imaging; pathology; radiography; retroperitoneal tumor